Explanation + Answer: First, 1 Liter equals 1,000 Milliliters.
If you need 300 liters to Milliliters, we need to do multiplication.
You need to think, 300 x 1000= ?
Well 3 x 1 = 3 and add 5 zeroes, 300000 mL.
Hope this helps.
Answer:
It is already rounded there. The answer is still 34.25
Step-by-step explanation:
i just did a quiz and i got it right
Lot cost x dollars.
Lot = $x
House costs $600 more than 12 times the lot
House = $600 + 12x
---------------------------------------------------------------
Answer: House = $600 + 12x . (Answer A)
---------------------------------------------------------------
![\frac{2}{3} - \frac{1}{x} = \frac{5}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3%7D%20-%20%5Cfrac%7B1%7D%7Bx%7D%20%3D%20%5Cfrac%7B5%7D%7B6%7D%20)
Multiply both sides by 3
![2 - \frac{1(3)}{x} = \frac{5(3)}{6}](https://tex.z-dn.net/?f=2%20-%20%5Cfrac%7B1%283%29%7D%7Bx%7D%20%3D%20%5Cfrac%7B5%283%29%7D%7B6%7D%20)
Simplify the numerators
![2 - \frac{3}{x} = \frac{15}{6}](https://tex.z-dn.net/?f=2%20-%20%5Cfrac%7B3%7D%7Bx%7D%20%3D%20%5Cfrac%7B15%7D%7B6%7D%20)
Multiply both sides by 6
![12 - \frac{3(6)}{x} = 15](https://tex.z-dn.net/?f=12%20-%20%5Cfrac%7B3%286%29%7D%7Bx%7D%20%3D%2015)
Simplify the numerator
![12 - \frac{18}{x} = 15](https://tex.z-dn.net/?f=12%20-%20%5Cfrac%7B18%7D%7Bx%7D%20%3D%2015)
Multiply both sides by x
12x - 18 = 15x Subtract 12x from both sides
-18 = 3x Divide both sides by 3
-6 = x Switch the sides to make it easier to read
x = -6
Check your answer by plugging -6 in for the x in the original problem:
![\frac{2}{3} - \frac{1}{x} = \frac{5}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3%7D%20-%20%5Cfrac%7B1%7D%7Bx%7D%20%3D%20%5Cfrac%7B5%7D%7B6%7D%20)
Plug in -6 for x
![\frac{2}{3} - \frac{1}{-6} = \frac{5}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3%7D%20-%20%5Cfrac%7B1%7D%7B-6%7D%20%3D%20%5Cfrac%7B5%7D%7B6%7D%20)
Change
![\frac{2}{3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B3%7D%20)
to
![\frac{4}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%7D%7B6%7D%20)
so all denominators are the same
![\frac{4}{6} - \frac{1}{-6} = \frac{5}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%7D%7B6%7D%20-%20%5Cfrac%7B1%7D%7B-6%7D%20%3D%20%5Cfrac%7B5%7D%7B6%7D%20)
Change
![\frac{1}{-6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B-6%7D%20)
to
![\frac{-1}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-1%7D%7B6%7D%20)
for easier work
![\frac{4}{6} - \frac{-1}{6} = \frac{5}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%7D%7B6%7D%20-%20%5Cfrac%7B-1%7D%7B6%7D%20%3D%20%5Cfrac%7B5%7D%7B6%7D%20)
Subtract the numerators (4 - (-1) )
![\frac{5}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B5%7D%7B6%7D%20)
=
![\frac{5}{6}](https://tex.z-dn.net/?f=%20%5Cfrac%7B5%7D%7B6%7D%20)
So,
x = -6 .
Hey there!
Use this formula:
![a^{-b} =\frac{1}{a^{b} }](https://tex.z-dn.net/?f=a%5E%7B-b%7D%20%3D%5Cfrac%7B1%7D%7Ba%5E%7Bb%7D%20%7D)
Remember this formula.
Now, let's solve the given problem.
![5^{-9} =\frac{1}{5^{9} }](https://tex.z-dn.net/?f=5%5E%7B-9%7D%20%3D%5Cfrac%7B1%7D%7B5%5E%7B9%7D%20%7D)
Hope this helps you!
~Just a joyful teen
![SilentNature](https://tex.z-dn.net/?f=SilentNature)
Hope this helps and have a fantabulous day! :)